Impact of coronary artery stent edge dissections on long‐term clinical outcome in patients with acute coronary syndrome: An optical coherence tomography study. Issue 2 (17th February 2015) - Bouki, Konstantina P.; Sakkali, Eleni; Toutouzas, Konstantinos; Vlad, Delia; Barmperis, Dimitrios; Phychari, Stavroula; Riga, Maria; Apostolou, Thomas; Stefanadis, Christodoulos
<x xml:space="preserve">Abstract</x> Aims The purpose of the present study was to assess the incidence, predictors and long term prognosis of stent edge dissections identified by (OCT) after the implantation of bare metal (BMS) and drug eluting stents (DES). Methods and Results We studied 74 patients who underwent percutaneous coronary intervention (PCI) because of an acute coronary syndrome. Edge dissections were found in 29 of 74 patients (39.1%). Independent predictors of edge dissections were: the presence of ST‐elevation myocardial infarction (STEMI) (P = 0.005, odds ratio 11.78; 95% Cl 2.06–67.10), the small reference lumen diameter (P = 0.009, odds ratio 0.11; 95% Cl 0.02–0.58) and the short stents implanted (P = 0.013, odds ratio 0.83; 95% Cl 0.72–0.96). During a follow‐up period of 25.6 ± 9.4 months 11 patients presented with at least one major adverse cardiac event. Event free survival was significantly decreased in patients with edge dissection with a flap thickness >0.31 mm compared to patients with thinner flap or without any dissection (P < 0.001). Conclusions OCT frequently detects edge dissections, usually related to STEMI presentation and to PCI technique. Deep vessel wall injury at stent edges with a dissection flap thickness more than 0.31mm carries an adverse clinical impact on long‐term clinical outcome. © 2015 Wiley Periodicals, Inc.